2017
DOI: 10.1038/s41598-017-03969-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sub-compartmental targeting and folding properties of the Prion-like protein Shadoo

Abstract: Shadoo (Sho), a member of prion protein family, has been shown to prevent embryonic lethality in Prnp 0/0 mice and to be reduced in the brains of rodents with terminal prion diseases. Sho can also affect PrP structural dynamics and can increase the prion conversion into its misfolded isoform (PrPSc), which is amyloidogenic and strictly related to expression, intracellular localization and association of PrPC to lipid rafts. We reasoned that if Sho possesses a natural tendency to convert to amyloid-like forms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 56 publications
(103 reference statements)
11
24
0
Order By: Relevance
“…GT1 cells grown on dishes were cooled on ice and biotinylated with NHS-LC-Biotin at 4 • C (as previously indicated [57,58]. Cells were lysed for 20 min using buffer 1 (25 mM Tris-HCl pH 7.5), 150 mM NaCl, 5 mM EDTA, 1% TX-100).…”
Section: Biotinylation Assaymentioning
confidence: 99%
“…GT1 cells grown on dishes were cooled on ice and biotinylated with NHS-LC-Biotin at 4 • C (as previously indicated [57,58]. Cells were lysed for 20 min using buffer 1 (25 mM Tris-HCl pH 7.5), 150 mM NaCl, 5 mM EDTA, 1% TX-100).…”
Section: Biotinylation Assaymentioning
confidence: 99%
“…In vitro experiments with amyloid fibrils and artificial membrane matrices show that lipid‐fibril interactions can affect formation of biological membranes . It has been recently reported that Shadoo (Sho), a partially proteinase K (PK)‐resistant and aggregation prone member of prion protein family, associates with lipid rafts and some of it can be found to localize at the ER . Therefore, it will be interesting to see how cytosolic aggregates can affect lipid composition of different endomembranes and how this is affected by the presence of non‐translocated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although various misfolded GPI-APs accumulate after proteasome inhibitor treatment, suggesting that the ERAD is involved in their turnover [ 6 , 13 , 21 , 22 ], it has been reported that misfolded GPI-anchored proteins do not pass through the canonical ERAD pathway but seem to be targeted to the alternative ER stress-induced pathway called RESET [ 23 ]. Thanks to RESET, misfolded GPI-APs dissociate from resident ER chaperones, leaving the ER and accessing the cell surface transiently before degradation in lysosomes ( Figure 1 B).…”
Section: Er/golgi Quality Control and The Role Of Gpi-anchor In Prmentioning
confidence: 99%